Eficacia de diferentes insecticidas comerciales para el control de Dalbulus maidis en el cultivo de maíz (Zea mays L.)” - Borja Freile , Cesar Sebastián (2023)
The maize leafhopper (Dalbulus maidis) is an insect that feeds on the sap of maize plants and other grasses, it is an important vector of diseases. One of the diseases that can cause economic losses of 60% to 80% is known as corn stunt which is caused by a spiroplasma (Spiroplasma kunkelii). Although there are various synthetic insecticides available on the market for pest control, very few specify the proper dosage and product for the control of D. maidis. Therefore, the objective of this research was to evaluate the efficiency of different commercial insecticides for the control of D. maidis in maize (Zea mays L.). The experiments were conducted at the Experimental Campus "La María" which belongs to Universidad Técnica Estatal de Quevedo. A randomized complete block design was used with three blocks and twelve treatments. Based on the obtained results; the insecticides Acetalaq, Aggressor, Fidelity, Fastac Duo, Engeo, Imunit and Sparko modified the population fluctuation of D. maidis. The Fastac Duo insecticide (0.45 cc/L + Dash MSO Max 0.32 cc/L) and the Imunit insecticide (0.51 cc/L + Dash MSO Max 0.38 cc/L) achieved the highest percentage of efficacy in the control of D. maidis in the first and second insecticides application in the maize crop with 62.6% and 72.2% respectively. The yield of the maize crop was similar among the evaluated treatments with results that are between 2947, 92 kg/ha and 3822.22 kg/ha. Keywords: control, neonicotinoids, pyrethroids, Spiroplasma kunkelii.